Rockin' around the chickadee - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries, 2024)
"Bells are ringing and alarms are sounding in Donna Andrews' latest cheery addition in the New York Times bestselling Meg Langslow series. Meg's sister-in-law, Delaney is pregnant. Since her due date is on or around Christmas Day, this is putting a bit of a damper on the usual holiday festivities. Meg and Michael are NOT hosting the usual house full of relatives and parties. Instead, Meg, along with her mother, her grandmother, her cousin Rose Noire, and her good friend Caroline, are militantly doing everything they can think of to keep Delaney quiet and healthy. All the relatives are farmed out to friends and neighbors; all the parties are being held somewhere else, and while Delaney is bored and mutinous, she's doing well, and they're managing to maintain a serene, peaceful environment for her . . . until a body is found in Meg and Michael's yard. Can Meg still keep Delaney calm in the middle of a murder investigation, all while trying to catch the killer? Full of her usual twists and turns, paired with relatable family holiday drama and Caerphilly's traditional Christmas merriment, Donna Andrews brings readers another joyful classic"--